Colorectal submucosa thickness in specimens obtained by EMR versus ESD: a retrospective pilot study - Clees, Natalie; Várnai-Händel, Alinda D.; Hildenbrand, Ralf; Grund, Karl-E.; Metter, Klaus; Dumoulin, Franz Ludwig (Endoscopy International Open, 2022)
Accurate histopathology is the mainstay for reliable classification of resected early colorectal cancer lesions in terms of potential risk of lymph node metastasis. In particular, thickness of resected submucosa is important in cases of submucosal invasive cancer. Nevertheless, little is known about the quality and thickness of submucosal tissue obtained using different endoscopic resection techniques. In this small pilot study, we performed morphometric analysis of submucosal thickness in specimens obtained from right-sided colorectal lesions using endoscopic mucosal resection (EMR) versus endoscopic submucosal resection (ESD). Comparative measurements showed significant differences in submucosal area ≥ 1000 μm and minimum submucosal thickness per tissue section analyzed (EMR vs. ESD: 91.2 % ± 6.6 vs. 47.1 % ± 10.6, P = 0.018; 933.7 µm ± 125.1 vs. 319.0 µm ± 123.6, P = 0.009). In contrast, no significant differences were observed in variation coefficient and mean maximum submucosal thickness. Thus, unexpectedly, in this small retrospective pilot study, specimens obtained using EMR had a better preserved submucosal layer than those obtained using ESD – possibly due to the different methods of specimen acquisition. The findings should be kept in mind when attempting to resect lesions suspicious for submucosal invasive cancer.